Feminist Legal Theory as a Review of Legal Philosophy: Its Relation with Gender Equality in Indonesia - Marita, Marita; Pramesti, Yustisia Pratiwi (Universitas Muhammadiyah Surakarta, 2023)
The birth of the Feminist Legal Theory is caused by an imbalance in the legal order which tends to be patriarchal, including in writing history the role of women should be balanced with that of men. In the perspective of legal philosophy, fulfilling women’s right and gender equality is an effort to obtain justice as al legal goal to realize the principle of equality before the law. The research method is normative juridical research with a qualitative analysis approach using primary and secondary legal sources . As a conclusion that the need for equal participation for women and men to exercise their rights and obligations in every policy and program as well as legal norms in laws and regulations that can guarantee equality of policies and programs that provide benefits to men and women.